2020
DOI: 10.3390/ma13225256
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Design of Boron Nitride-Based Membranes with Armchair and Zigzag Nanopores for Efficient Water Desalination

Abstract: Recent studies have shown that the use of membranes based on artificial nanoporous materials can be effective for desalination and decontamination of water, separation of ions and gases as well as for solutions to other related problems. Before the expensive stages of synthesis and experimental testing, the search of the optimal dimensions and geometry of nanopores for the water desalination membranes can be done using computer-aided design. In the present study, we propose and examine the assumption that rect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Besides the above-mentioned 2D nanosheets, hBN nanosheets have also been investigated as separation membranes by various researchers. ,,,,,, Chen et al experimentally examined the water transport performance of amino-functionalized nanoporous hBN using a positive pressure setup. They found that the hBN membranes are highly stable in various organic solvents and water and showed high water flux and excellent selectivity in organic and aqueous solvents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the above-mentioned 2D nanosheets, hBN nanosheets have also been investigated as separation membranes by various researchers. ,,,,,, Chen et al experimentally examined the water transport performance of amino-functionalized nanoporous hBN using a positive pressure setup. They found that the hBN membranes are highly stable in various organic solvents and water and showed high water flux and excellent selectivity in organic and aqueous solvents.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it was even higher than that through nanoporous graphene. Other studies focusing on unraveling the role of doping, nanopore edge functionalization, ,, and edge type in modulating water permeation have also been carried out. Nevertheless, in the above-mentioned studies, the electrical potential produced by nanoporous hBN was not validated with quantum–mechanical DFT calculations, although the charges on B and N atoms were derived using some DFT-based charge partitioning schemes.…”
Section: Introductionmentioning
confidence: 99%